FACTORS RELATED TO NURSE’S RESPONSE TIME IN HANDLING OF EMERGENCY PATIENTS - Andi Syamsul Bachri Jamal; Desak Nyoman Suartini; Anas Budi (Nurse and Health: Jurnal Keperawatan, 2021)
Background: In emergency care, the most important thing to note is the speed of nurses in responding or acting on the first patient who enters the emergency room. This speed is often referred to as response time. Nurse response time is always a measure of the service quality of a hospital or health center. Response times depend on the speed available as well as the quality of assistance to save lives/prevent disability. Objectives: The study aimed to determine the factors related to the response time of nurses in the handling of emergency patients at Lagaligo I Hospital, East Luwu. Methods: Carrying out the research is from June to August 2020. Analytical survey design with a cross-sectional approach. The research subjects were 24 nurses. measuring tools, namely questionnaires. analysis used bivariate analysis used the Chi-Square Test. Results: This shows that there is a relationship between education and response time with a value of p-value = .013, knowledge and response time with a value of p-value = .001, the length of work and response time with a value of p-value = .000, and training and response time with p-value = .006. Conclusion: The education level of health workers is getting higher. Of course, knowledge and experience also increase, on average they are in their work longer so they are more productive and nurses have attended several pieces of training to improve their competencies.